HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU PENCEGAHAN DINI KANKER SERVIKS PADA PASIEN DI KLINIK SEROJA KOTA KEDIRI - Sari, Shinta Lutfiana (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Knowledge is the result of knowing and sensing that occurs after the person commits to a particular object . Knowledge in the cognitive domain has six levels, they are known, understanding, applications, analysis, synthesis, evaluation. Know-ledge can influence behavior, where behavior is an act or event from the man himself who has a vast expanse, among others: walk, talk, cry, laugh, work, study, write, read, and other. Early prevention behavior of cervical cancer can be done through primary prevention or early prevention and secondary prevention of cancer with a pap smear test.This study uses an observational study design and analytical survey by cross sectional approach. Population of more than 115 people and then taken using accidental sampling and obtained a sample of 90 persons. Data collection level of knowledge and behavior are using a questionnaire. Data were collected simul-taneously and after the data collected then analyzed by Spearman rho test statistic. The results of data analysis using Spearman rho test statistic at α = 0.05 is obtained with the significant value of 0.045 for the area of knowing and early prevention of behavior, the significant value of 0.008 for the area of understanding and early prevention behavior of cervical cancer, and the significant value of 0.000 for the application domains and early prevention behavior of cervical cancer. Because of significant results, there is correlation between knowledge and early cervical cancer prevention behavior patients at Clinic Seroja Kediri. It is expected patient in Seroja Clinic Kediri realize the importance of maintaining cleanliness of the vagina and perform routine inspections to determine health of genitals.